Biochemical Properties of Banana and Pineapple Intercropped in Organically Managed Young Arecanut Based Cropping System - Chettri, Sandeep; Bhowmick, Nilesh; Medda, Partha Sarathi; Ojha, Sankalpha; Banik, Ganesh Chandra; Bhattacharjee, Himadri (International Journal of Economic Plants, 2025)
The present investigation was carried out at the instructional and research field of the Department of Plantation Crops and Processing, Faculty of Horticulture, Uttar Banga Krishi Viswavidyalaya, Pundibari during the Month of March 2019–20 to 2020–21, to study the influence of organic treatments on biochemical properties of banana (Musa sp., cv. Grand Naine) and pineapple (Ananas comosus cv. Kew) grown in an organic arecanut-based cropping system. The experiment was carried out in a Randomized Block Design with four replications for estimating the biochemical properties of banana and pineapple viz. total soluble solids (°Brix), total sugar (%), reducing sugar (%), titrable acidity (%) and ascorbic acid (mg 100 g-1) against six differently formulated organic treatments. Results revealed that among five different treatments, N5 (vermicompost @ 2.0 kg plant-1 year-1 in banana and 18 kg plot-1 of 9.0 m² in pineapple along with biofertilizers i.e. Azotobacter +Azosperillium+PSB+VAM+Trichoderma) exhibited the highest value for TSS (23.07°Brix and 17.96°Brix in banana and pineapple), total sugar content (18.28% and 12.36% in banana and pineapple), reducing sugar content (9.28% and 2.99% in banana and pineapple) and ascorbic acid content (10.69 mg 100 g-1 and 34.69 mg 100 g-1 in banana and pineapple), respectively. These highlights the benefits of organic based cropping system with regard to biochemical properties of banana and pineapple intercropped under young arecanut plantations.